The individualists : radicals, reactionaries, and the struggle for the soul of libertarianism - Zwolinski, Matt; Tomasi, John, 1961- (Princeton, USA; Oxford, UK: Princeton University Press, 2023)
"Is libertarianism a progressive doctrine, or a reactionary one? Does libertarianism promise to liberate the poor and the marginalized from the yoke of state oppression, or does talk of "equal liberty" obscure the ways in which libertarian doctrines serve the interests of the rich and powerful? Through an examination of the history of libertarianism, this book argues that the answer is (and always has been): both. In this book we explore the neglected 19th century roots of libertarianism to show that it emerged first as a radical and progressive doctrine. Libertarianism took a conservative turn in the 20th century primarily as a reaction against the rise of state socialism. Now, with international communism no longer a threat, libertarianism is in the midst of an identity crisis, with progressive and reactionary elements struggling to claim the doctrine as their own, most notably on issues of race. This book tells the history of libertarianism through an examination of six defining themes: private property, skepticism of authority, free markets, individualism, spontaneous order, and individual liberty. In doing so, it reveals that history to be longer, wider, and considerably more diverse than is commonly believed. It is a history full of internal tensions, idiosyncratic personalities, and surprising arguments. It is a history of the men (and sometimes women) who called themselves: The Individualists"--
"A sweeping history of libertarian thought, from radical anarchists to conservative defenders of the status quoLibertarianism emerged in the mid-nineteenth century with an unwavering commitment to progressive causes, from women's rights and the fight against slavery to anti-colonialism and Irish emancipation. Today, this movement founded on the principle of individual liberty finds itself divided by both progressive and reactionary elements vying to claim it as their own. The Individualists is the untold story of a political doctrine continually reshaped by fierce internal tensions, bold and eccentric personalities, and shifting political circumstances.Matt Zwolinski and John Tomasi trace the history of libertarianism from its origins as a radical progressive ideology in the 1850s to its crisis of identity today. They examine the doctrine's evolution through six defining themes: private property, skepticism of authority, free markets, individualism, spontaneous order, and individual liberty. They show how the movement took a turn toward conservativism during the Cold War, when the dangers of communism at home and abroad came to dominate libertarian thinking. Zwolinski and Tomasi reveal a history that is wider, more diverse, and more contentious than many of us realize.A groundbreaking work of scholarship, The Individualists uncovers the neglected roots of a movement that has championed the poor and marginalized since its founding, but whose talk of equal liberty has often been bent to serve the interests of the rich and powerful"--
Introduction -- What is Libertarianism? -- Three Eras of Libertarian Thought -- Land, Labor, and Ownership: The Right of Private Property -- Demystifying the State: Libertarian Anarchism -- Big Business and Free Markets -- Poverty & Spontaneous Order -- Racial Justice and Individualism -- Global Justice and Non-Intervention -- Conclusion.
Includes bibliographical references and index.
Keywords: Libertarianism; POLITICAL SCIENCE / Political Ideologies / Libertarianism; PHILOSOPHY / Political